LAPAROSCOPIC AND OPEN MESH REPAIR OF VENTRAL HERNIAS: A RANDOMIZED CLINICAL TRIAL - Kiani, Muhammad Ali; Razzaq, Zeeshan; Afzal, Muhammad (Journal of Postgraduate Medical Institute, 2014)
Objective: To compare the operative time and post-operative pain in laparoscopicand open mesh repair of ventral hernias. Methodology: From October, 2010 to February, 2011 in surgery department,Holy Family hospital, Rawalpindi. In this Randomized Clinical Trial a total of160 patients were included after taking approval from hospital ethical committeeand informed written consent from each patient. The admitted patientsfor elective surgical repair of ventral hernia were randomly allocated to Group A (laparoscopy) and B (open repair). Information regarding operative time andpain scores after 12, 24 and 72 hours of surgery was recorded. Results: In group A, the mean age was 41.10 ± 8.98 years and in group B41.23 ± 9.18 years. There were 36 (22.25%) male patients. There were 18(11.3%) patients of Incisional, 107 (66.9%) patients of umbilical/paraumbilical and 35(21.9%) patients of Epigastric hernia in this study. In group A, the meanoperative time was significantly (p-value= 0.000) less (66.56 ± 16.14 minutesvs. 71.21 ± 12.91 minutes) as compared to group B. There was no differencein mean pain score at 12th hour (p-value= 0.797). At 24th hour and 72nd hourthe mean pain score in Laparoscopic group was significantly (p-value = 0.000)lower. Conclusion: Laparoscopic management of ventral hernia resulted in short operativetime, less pain at 24th and 72th hours. So it should be considered asthe procedure of choice for ventral hernia repair.